2022
DOI: 10.3389/fneur.2022.963648
|View full text |Cite
|
Sign up to set email alerts
|

Night blood pressure variability, brain atrophy, and cognitive decline

Abstract: BackgroundAlthough blood pressure variability (BPV) has emerged as a novel risk factor for Alzheimer's disease, few studies have examined the effects of night BPV on brain structure and function. This study investigated the association of night BPV with brain atrophy and cognitive function changes.MethodsThe analysis included 1,398 participants with valid ambulatory blood pressure (BP) monitoring at baseline and both baseline and 4-year follow-up brain magnetic resonance images who were recruited from the Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Additionally, daytime systolic BPV, but not nighttime BPV, was reduced in the intensive treatment group and was predictive of probable dementia in the standard treatment group. The present findings add information about clinical diagnosis to previous observational studies linking BPV via ambulatory monitoring to cognitive decline typically measured with single tests of cognition ( 1 , 23 27 ). Additionally, the current study used data from a cohort with rigorously controlled mean BP levels, which enabled us to assess the contribution of BPV vs mean BP to dementia risk at a level not typically available in observational cohorts.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Additionally, daytime systolic BPV, but not nighttime BPV, was reduced in the intensive treatment group and was predictive of probable dementia in the standard treatment group. The present findings add information about clinical diagnosis to previous observational studies linking BPV via ambulatory monitoring to cognitive decline typically measured with single tests of cognition ( 1 , 23 27 ). Additionally, the current study used data from a cohort with rigorously controlled mean BP levels, which enabled us to assess the contribution of BPV vs mean BP to dementia risk at a level not typically available in observational cohorts.…”
Section: Discussionsupporting
confidence: 65%
“…This method has the added benefits of monitoring an individual’s BP in their everyday environment (vs clinic setting) and reducing the potential for white-coat hypertension or masked hypertension ( 7 , 22 ). Several observational studies of BPV via ambulatory monitoring suggest links with cognitive decline ( 1 , 23 27 ) but relationships with dementia risk remain understudied. Additionally, no prior studies have investigated whether BPV over 24 hours may relate to risk for dementia under specific antihypertensive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing all revealed significant risk factors of ESUS described above, it can be concluded that the vast majority of them could be the consequences of AH. For instance, it was demonstrated that AH is strongly associated with small vessel diseases that clinically manifest as brain changes (cerebral microbleeds, brain atrophy, and the others) and cognitive deterioration that were found in our research [29][30][31][32]. It is also well known that AH may be the leading cause (however, not the only one) of the increased heart rate [33,34], conduction disturbance, elevated PASP [35], and heart atrial and ventricular remodeling [36][37][38], all of which were identified in ESUS patients in the current study.…”
Section: Discussionsupporting
confidence: 61%
“…Yu et al found that the volume of the temporal GM decreased by 0.039 for each unit increase in SBPV. 34 Elevated SBPV may lead to cognitive decline by damaging neurons. Although no similar previous studies have been conducted, a rat model of high BPV induced by performing sinoaortic denervation found that elevated BPV leads to extensive damage and loss of cardiomyocytes through an inflammatory response and then to the replacement of damaged cardiomyocytes through repair fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al. found that the volume of the temporal GM decreased by 0.039 for each unit increase in SBPV 34 . Elevated SBPV may lead to cognitive decline by damaging neurons.…”
Section: Discussionmentioning
confidence: 99%